Catálise por heteropoliácidos na valorização de biorrenováveis: acetilação de 1,4-cineol e 1,8-cineol (eucalyptol) em solventes sustentáveis - Núbia Luiza Lataliza Carvalho (2024)
1,4-cineole and 1,8-cineole are monoterpenic ethers found in eucalyptus essential oils. Despite the annual production of these oils reaching millions of tons, these compounds are still underexplored as raw materials. This study focused on the valorization of 1,4-cineole and 1,8-cineole to produce value-added products through the reaction of acetylation with acetic anhydride. The process was performed in green solvents under environmentally friendly conditions using the cesium salt of phosphotungstic acid, Cs2.5H0.5PW12O40 (CsPW), as a heterogeneous catalyst. Acetylation of 1,4-cineole and 1,8-cineole resulted in the mixtures of terpenyl acetates, monoterpenic esters of a significant interest for the fragrance industry. The nature of the solvent directly influenced the composition of the mixtures, enabling the production of terpenyl acetates in different proportions. Consequently, it was possible to obtain mixtures with different aroma characteristics that can be directly utilized as fragrance ingredients without separation of individual compounds. Thus, in this work it was developed a novel synthetic route for the valorization for 1,4-cineole and 1,8-cineole, abundant and cost effective natural raw materials, under industrially and environmentally favorable reaction conditions, allowing for the production of high value products with a potential for the application in the Fine Chemicals industry.